Photographic & Cephalometric Analysis of Craniofacial Structures in Indian Population - A Correlative Study - Sharma, Shreya; Sunil, M.K; Kumari, Archana; Potsangbam, Tarishma; Sharma, Kanchan; Sinha, Ritama (Journal of Neonatal Surgery, 2025)
Background- Radiographic cephalometrics and photographic systems are the most suitable and therefore the most commonly used. Not only can they provide points and landmarks for measurements, but they can also offer an analytical and complete evaluation of the unique craniofacial aspect of the person who is being investigated. Materials and method- Standardized right profile photographs of subjects were taken in the Natural Head Position (NHP), with maximum intercuspation and lips at rest. Digital Lateral skull radiographs were taken with CS 8100 (Carestream Dental). The exposure parameters for the digital cephalographs are 74kV, 8mA and 10secs. The radiographic and photographic measurements was analysed with Digimizer (Medcalc Software, version – 4.6.1.0) image analysis software for windows. The software calculated all the measurements once all the landmarks were properly identified on each record that had been previously scaled to life size. Result- A’N’B’ shows the greatest correlation to its analogous cephalometric measurement ANB (r = 0.65) in sagittal assessment and in vertical assessment FMA’ shows the greatest correlation (r = 0.67). Lowest coefficients were obtained for A’-B’ Perp(r = 0.33) in saggital assessment and AFH’(r = 0.37) in vertical assessment. ‘ In linear regression analysis where A’N’B(r2 = 0.67) and FMA’(r2 = 0.68) shows the best results. Lower values were obtained in A’-B’ Perp(r2 = 0.17) and AFH’(r2 = 0.22). Conclusion- photographic analysis could be used as an alternative when cephalograms cannot be obtained due to lack of availability of equipment concerns with radiation exposure and in analysis of large number of samples in epidemiological studies